AUREOCHROME, a photoreceptor required for photomorphogenesis in stramenopiles - Takahashi, Fumio; Yamagata, Daisuke; Ishikawa, Mié; Fukamatsu, Yosuke; Ogura, Yasunobu; Kasahara, Masahiro; Kiyosue, Tomohiro; Kikuyama, Munehiro; Wada, Masamitsu; Kataoka, Hironao (Proceedings of the National Academy of Sciences - PNAS, 2007)
A blue light (BL) receptor was discovered in stramenopile algae Vaucheria frigida (Xanthophyceae) and Fucus distichus (Phaeophyceae). Two homologs were identified in Vaucheria; each has one basic region/leucine zipper (bZIP) domain and one light-oxygen-voltage (LOV)-sensing domain. We named these chromoproteins AUREOCHROMEs (AUREO1 and AUREO2). AUREO1 binds flavin mononucleotide via its LOV domain and forms a 390-nm-absorbing form, indicative of formation of a cysteinyl adduct to the C(4a) carbon of the flavin mononucleotide upon BL irradiation. The adduct decays to the ground state in [almost equal to]5 min. Its bZIP domain binds the target sequence TGACGT. The AUREO1 target binding was strongly enhanced by BL treatment, implying that AUREO1 functions as a BL-regulated transcription factor. The function of AUREO1 as photoreceptor for BL-induced branching is elucidated through RNAi experiments. RNAi of AUREO2 unexpectedly induces sex organ primordia instead of branches, implicating AUREO2 as a subswitch to initiate development of a branch, but not a sex organ. AUREO sequences are also found in the genome of the marine diatom Thalassiosira pseudonana (Bacillariophyceae), but are not present in green plants. AUREOCHROME therefore represents a BL receptor in photosynthetic stramenopiles.